Persepsi Individu Generasi Z Terkait Penerapan Strawless - Nur Rizky Dewi Angelita; Edi Dwi Riyanto; Nadya Afdholy (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
The strawless policy is believed to be an effort to prevent environmental problems in Indonesia. This campaign targets generation Z as a group that is closely related to the use of the internet and technological advances. The strawless campaign collaborated with Generation Z's coffee consumption lifestyle is expected to create a new culture. This research aims to find out generation Z’s views towards the strawless policy and examine the realization of strawless as a cultural element to create a new way of life. The researcher used qualitative methods with instruments of in-depth interview and observation. Data analysis uses circuit of culture theory by Stuart Hall (1997) consists by five aspects in examining cultural phenomena, namely regulation, representation, identity, production, consumption. The results of the study show that from the five elements of the circuit of culture, it proves that strawless has succeeded in becoming a new culture in the coffee activities of generation Z. However, many reviews and developments are still needed regarding regulations and other alternatives for the convenience of producers and consumers.